Efektivitas Permainan Ular Tangga Tematik Ḥadīqat al-Ḥayawānāt terhadap Penguasaan Mufrodat Bahasa Arab Siswa - Lailaa, Hikmatul; Azis, Putri Apriani; Jamal, Mardhiana (CV. Ulil Albab Corp, 2025)
Abstract: This study aims to analyse the effectiveness of the thematic Snakes and Ladders game حديقة الحيوانات in improving the Arabic vocabulary mastery of fifth-grade students at MIN 1 Gowa. Arabic vocabulary mastery is an important foundation for communication skills and understanding Islamic teachings. However, low vocabulary mastery among students poses a challenge in learning. To address this issue, an educational game that has been proven to increase student motivation and engagement was implemented. Through this study, the Snakes and Ladders game was formulated with a zoo theme relevant to the students' world. The research method used was a quantitative approach with a pre-experimental one-group pre-test post-test design. The results showed a significant increase in vocabulary mastery, with the average student score rising from 59 on the pre-test to 82 on the post-test, and all students successfully achieving the Minimum Competency Criteria (KKM). These findings confirm that the Thematic Snakes and Ladders game حديقة الحيوانات is effective in creating an interactive and meaningful learning experience for students, while also overcoming gaps in vocabulary mastery. Keywords: vocabulary; Arabic language; Snakes and Ladders game; Ḥadīqat al-Ḥayawānāt; learning outcomes